Avaliação da influência de aspectos socioambientais do alto da bacia do Rio Subaé sobre a qualidade das águas superficiais - Adorno, Erivaldo Vieira (2012)
Alterations in the quality, distribution and quality of the hydro resources endanger the human survival and the other species of the planet, as the economic and social development of the countries fundamented in the disponibility of good quality water and in the capability of its conservation and protection. In Brasil, although water is considered a abundant resource, there are really poor areas for those water becomes a limited resource to human needs. The high cost or river Subaé bay, Feira de Santana - BA surrounds an area of of 20.62 square kilometers and it is caracterized mainly for the demand of urban, industrial and agricultural uses, what reflects in the big pressure for the utilization of the superficial water to receptors for industrial efluents of Industrial Center of Subaé (CIS) and, mainly, domestic sewage coming from different neighborhood in Feira de Santana. The main goal of this research is to determine the socialenvironmental aspects of the high of river Subaé bay and evaluate the possible influence over the quality of superficial water. The methodology employed to reach the goal passed by the understanding of the impact of aspects socioenvironmental over the physic-chemistry indicated as important to evaluate the quality of superficial water. For this, there was and integration of information plans in place of Geografic Information System (GIS) and utilization of the Linear Regretion to determine the level of relation between these socioenvironmental aspects and the value of DO, BOD and Turbidity, found with the monitoring of the quality of water. Through the comparison of quality parameters of water analyzed and the disponible value in the environmental legislation its was possible to see that, mainly the nascents of river Subaé, are at risk. The monitoring of quality of water in the river Subaé bay and the utilization of new tools to the analysis of the quality of this environment allows the adoption of mesures of supression and/or reduction of the uses that create the environmental alterations in the region.